Fabrication and characterisation of fluidic based memristor sensor for liquid with hydroxyl group - Hadis, Nor Shahanim Mohamad; Manaf, Asrulnizam Abd; Ngalim, Siti Hawa; Herman, Sukreen Hana (Elsevier, 2017)
Two types of memristor sensor were fabricated using two different TiO2 deposition methods of sputtering and sol-gel spin coating. The surface morphology of the sensors and the behaviour of the sensors were analysed by using scanning electron microscopy with energy dispersive x-ray system and I-V characterisation system respectively. The sensors were applied with liquid with hydroxyl group to check the capability of this sensor in sensing different concentration of hydroxyl ion inside the liquid. For that purpose, D-glucose liquid with four concentrations of 10 mM, 20 mM, 30 mM and 40 mM were chosen. The liquids dispensed onto the TiO2 surface to act as sensing material. The TiO2 surface was initially covered with polydimethylsiloxane to control the liquid. The sensing capability of the sensors was determined via the current-voltage measurement and off-on resistance ratio. The sensitivity of the sensors was analysed from the off-on resistance ratio analysis. Type II memristor sensor which was fabricated using sol-gel spin coating technique recorded high sensitivity of 120.65 (mM)−1, while Type I sensor fabricated using the sputtering technique recorded low sensitivity of 0.035 (mM)−1. However, SEM-EDX image illustrated that the sputtering technique produced more uniform TiO2 thin film than sol-gel spin coating technique with larger atomic number of oxygen through the sol-gel spin coating technique. This indicates Type II sensor that has large number of oxygen atom produced more reaction with hydroxyl ion inside the liquid. While, Type I sensor produced less reaction compared with Type II and thus produced smaller off-on resistance ratio.